PENGARUH PENGGUNAAN KOLASE TERHADAP KEMAMPUAN MOTORIK HALUS ANAK USIA 4-5 TAHUN DI RA SAFINATUNNAJAH BAREGBEG CIAMIS - Nugraha, Anggi Purwa; Mulyono, Nono; Miswen, Miswen (Sekolah Tinggi Agama Islam Putra Galuh Ciamis, 2024)
This study is motivated by the fact that early childhood’s fine motor skill has not reached the expected level. Thus, the aim of this research is to determine the influence of using collage towards early childhood’s fine motor skill. This study used quantitative method under an experimental design using One Group Pretest-Posttest Design. The total sample was 8 early childhoods with a saturated sampling technique. The pre-test results showed that 63% of early childhood with the category not yet developed (BB), and 38% of early childhood were in the category beginning to Develop (MB). After using collage, the post-test results showed an increase with 50% of early childhoods reached the category develop according to expectation (BSH) and 50% of early childhood reached the category very well develop (BSB). Then, the results of testing hypothesis showed that the sig. (2-tailed) of 0.001 < 0.05, which means that H1 is accepted and H0 is rejected. Thus, it can be concluded that the use of collage has a positive influence towards early childhood’s fine motor skill at RA Safinatunnajah.